Effect of shell thickness on small-molecule solar cells enhanced by dual plasmonic gold-silica nanorods - Xu, Xiaoyan (2014)
Chemically synthesized gold (Au)-silica nanorods with shell thickness of 0 nm–10 nm were incorporated into the bulk heterojunction of a small-molecule organic solar cell. At optimal (1 wt. %) concentration, Au-silica nanorods with 5 nm shell thickness resulted in the highest power conversion efficiency of 8.29% with 27% relative enhancement. Finite-difference time-domain simulation shows that the localized electric field intensity at the silica shell-organic layer interface decreases with the increase of shell thickness for both 520 nm and 680 nm resonance peaks. The enhanced haze factor for transmission/reflection of the organic layer is not strongly dependent on the shell thickness. Bare Au nanorods yielded the lowest efficiency of 5.4%. Light intensity dependence measurement of the short-circuit current density shows that the silica shell reduces bimolecular recombination at the Au surface. As a result, both localized field intensity and light scattering are involved in efficiency enhancement for an optimized shell thickness of 5 nm.